Chapter Bluredness and punctum (Sasnal at the POLIN Museum) - Rejniak-Majewska, Agnieszka (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The text is devoted to the exhibition Wilhelm Sasnal: Such a Landscape presented in 2021 at the POLIN Museum in Warsaw. Presented not in an artistic institution, but in a place dedicated to memory and history, the exhibition has shed new light on Sasnal’s work, as an expression of his personal commitment to confronting the shadows of the past. The artist, the world-famous Polish painter, here positioned himself as a mediator, an intermediary, one who touches painful realities, but does not claim the title to instruct anyone. Sasnal’s interest in history and his references to Spiegelman’s Maus or Lanzmann’s Shoah had already been noticed before, but the exhibition in question has decidedly moved the perception of his work beyond identifying it with a play of quotations and exploring the possibilities of the painterly medium. The text analyses the exhibition’s arrangement, the selection of presented works, and the way of establishing connections between them. The importance of the illustrated guide accompanying the exhibition, including the artist’s comments and drawings is emphasized. The author also examines press reviews and interviews with the author and curator regarding the exhibition design and Sasnal’s working method. The subject of consideration is in particular the concept of “landscape” used in the title of the exhibition: its literal and figurative meanings, as well as the related problems of visibility, illegibility, and formlessness attempts – to approach what is present, but blurred: things painful and shameful in the collective memory.